Analysis of the Factors Causing Delay in Pile Foundation Work for Medium-Story Building Project - Rofi Henindia; Suroso, Agus (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Pile work in building construction is generally the first substructure/lower structure construction to be carried out. This is very important to note because delays in execution time at the beginning of the work will have a domino effect on increasing project costs. This study aims to analyze factors that cause delays in pile work (Xi) and on-time performance (Y) in constructing medium-rise buildings in the Jabodetabek area. This study uses the Multiple Linear Regression Analysis Method, with the data and information used are respondents' perceptions through questionnaires and statistically analyzed using the SPSS version 25 program. Simultaneously/together, Design/Planning Factors (X1), Work Implementation Factors (X2), Material Factor (X3), Equipment Factor (X4), and Soil Condition Factor (X8) have an influence contribution of 69% to the Time Performance of pile work in medium-rise building construction projects (Y). While the most dominant factor influencing the cause of delays in pile work in medium-rise building construction projects (Y) is the Soil Condition Factor (X8).